WEED CONTROL BY SOLARIZATION AND MULCHING IN COWPEA DEVELOPMENT - Maia Júnior, Sebastião de Oliveira; Andrade, Jailma Ribeiro de; Reis, Lígia Sampaio; Santos, Claudiana Moura dos; Silva, Lennon Kledson dos Santos; Martins, Gleica Maria Correia (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
Weeds are a serious threat to agriculture because they compete with crops, thereby interfering in production. As such, this study aimed to assess weed control using soil solarization and mulching on the growth and yield of cowpea. A completely randomized design was used, with eight treatments and four repetitions. The treatments consisted of a combination of two management practices, namely soil solarization (with and without) and three mulches (castor bean, rattlepod and spontaneous vegetation), as well as no mulching. Non-solarized soil and without mulch increased the number and dry weight of weeds, while the main stem length of the cowpea plants decreased. Mulching increased the pod length and number of seeds per pod regardless of solarization, as well as shoot dry weight and moisture content. By contrast, root dry weight increased in the absence of mulching, particularly in non-solarized soil. Soil solarization reduces weed infestation in cowpea crops, especially when associated with mulching.